2006
DOI: 10.4081/hi.2006.141
|View full text |Cite
|
Sign up to set email alerts
|

Antiatherogenic effects of n-3 fatty acids - evidence and mechanisms

Abstract: N-3 (omega-3) (polyunsaturated) fatty acids are thought to display a variety of beneficial effects for human health. Clues to the occurrence of cardiovascular protective effects have been, however, the spur for the first biomedical interest in these compounds, and are the best documented. Historically, the epidemiologic association between dietary consumption of n-3 fatty acids and cardiovascular protection was first suggested by Bang and Dyerberg, who identified the high consumption of fish, and therefore, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…On a human nutrition perspective, these fatty acids can be beneficial as they can be converted to fatty acids with 20 carbon atoms, like arachidonic acid (C20:4 omega-6) and eicosapentaenoic acid (C20:5 omega-3) [59]. Nevertheless, arachidonic acid, derived from linolenic acid, may enhance blood platelet aggregation; hence, it can increase the coronary risk [60]. Arachidonic acid has the potential to partially block the conversion of omega-6 FAs to harmful eicosanoids.…”
Section: Plos Onementioning
confidence: 99%
“…On a human nutrition perspective, these fatty acids can be beneficial as they can be converted to fatty acids with 20 carbon atoms, like arachidonic acid (C20:4 omega-6) and eicosapentaenoic acid (C20:5 omega-3) [59]. Nevertheless, arachidonic acid, derived from linolenic acid, may enhance blood platelet aggregation; hence, it can increase the coronary risk [60]. Arachidonic acid has the potential to partially block the conversion of omega-6 FAs to harmful eicosanoids.…”
Section: Plos Onementioning
confidence: 99%
“…Long-chain omega-3 polyunsaturated fatty acids , namely eicosapentaenoic and docosahexaenoic acids (EPA and DHA), have recognized antiatherogenic properties (De Caterina and Zampolli 2006). These have been mainly attributed to their hypolipidemic effect but several lines of evidence show that LC-x3PUFAs can reduce atherosclerosis independently of the systemic risk factors, suggesting direct anti-atherogenic action of LC-x3PUFAs at the vascular level (Ishikado et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, higher intake of SFA is frequently reported to be a risk factor of IHD as a pro-atherogenic factor [ 31 ]. However, this study failed to identify a significant relation, other studies indicated that there is SFA had an adverse effect on IHD by increasing the total blood cholesterol concentration [ 32 ] and eventually increase the risk of ischemic stroke [ 33 – 35 ].…”
Section: Discussionmentioning
confidence: 99%